2007
DOI: 10.1055/s-2007-963426
|View full text |Cite
|
Sign up to set email alerts
|

Mysterium Ligamentum alare Ruptur: Stellenwert der MRT-Diagnostik des Schleudertraumas - biomechanische, anatomische und klinische Studien

Abstract: Biomechanical studies give no evidence of alar ligament involvement in whiplash disease. Using MRI, signal alterations of alar ligaments can hardly be differentiated from common normal variants. Functional MRI provides no diagnostic yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…None of the participants in the traumatic group had a diagnosis of alar ligament damage prior to high-field strength MRI. This would suggest that the diagnosis of an alar ligament lesion remains challenging [5,8,21,22], unless highly specialized MRI machines and protocols are followed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the participants in the traumatic group had a diagnosis of alar ligament damage prior to high-field strength MRI. This would suggest that the diagnosis of an alar ligament lesion remains challenging [5,8,21,22], unless highly specialized MRI machines and protocols are followed.…”
Section: Discussionmentioning
confidence: 99%
“…The alar ligaments are important stabilizers of the cervical spine and may become damaged following trauma, hence require careful examination, particularly in patients who present with neck-related problems with a history of injury [1,2]. The gold standard for determining alar ligament damage is MRI [3,4] for which there is a growing body of evidence supporting its use [5][6][7]. New technical developments in MRI such as high-fidelity 3-T MRI [8] and improved protocols [9] provide better visualization of the alar ligaments than previous MRI methods [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…concluded that MRI signal differences in the alar ligaments could not be differentiated from normal variants. [33]…”
Section: Discussionmentioning
confidence: 99%
“…The validity of these tests in the detection of vertebral or carotid artery dissection is questionable, due to their poor sensitivity and specificity that has led some authors to suggest abandoning their routine use as screening tests. 6,19,20,55 The SharpPurser test has been shown to have good reliability and validity for the detection of sagittal plane instability (integrity of transverse ligament) of C1-2, when compared to the gold standard of lateralview cervical flexion stress radiographs, in individuals with rheumatoid arthritis. However, there is only minimal evidence on the reliability or validity of other physical examination procedures that are used to detect CCJ hypermobility in other planes of motion, such as the lateral shear test and palpation of C2 spinous process rotation with neck lateral flexion.…”
Section: Physical Examination Proceduresmentioning
confidence: 99%